Editorial: Sustainable and resilient food systems in times of crises - Ben Hassen, Tarek; El Bilali, Hamid; Daher, Bassel; Burkart, Stefan (Frontiers Media, 2025)
The global food system is facing multiple and multifaceted challenges and crises: increasing population, climate change, pandemics, conflicts, economic shocks, and natural disasters. These challenges have exposed its fragility and underscored the urgency of transitioning to sustainable and resilient food systems. Such systems ensure equitable access to nutritious food, minimize environmental impacts, and enhance resilience against shocks. In crises like the COVID-19 pandemic and the ongoing conflict in Ukraine, the vulnerabilities of the global food system have become starkly apparent, leading to disruptions in supply chains, food shortages, and inflation. Additionally, climate change and natural disasters further threaten food security worldwide. This Research Topic explores innovative approaches—including agroecological practices, circular economies, and localized food systems—to build resilience and sustainability. To provide a comprehensive understanding of these pressing issues, the 17 articles of this Research Topic are organized into four thematic areas: the impacts of crises on food systems, the effects of COVID-19 on food systems, sustainable food systems and practices, and the social, economic, and waste management dimensions of food systems.